A Review of Offences Against Women under the Indian Penal Code (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper reviews the offences against women under the Indian Penal Code (IPC), with a particular focus on the challenges posed by digital platforms and the misuse of social media. The study explores provisions related to modesty, sexual harassment, stalking, defamation, human trafficking, identity theft, and other offences that disproportionately impact women. Case laws and judicial interpretations are highlighted to demonstrate how courts have addressed such violations and balanced them with constitutional rights such as freedom of speech and privacy. The paper also examines the significance of the Criminal Law (Amendment) Act, 2013, which introduced reforms in response to increasing violence against women and emerging cybercrimes. By analysing legal provisions, precedents, and contemporary examples, this review underscores the evolving nature of crimes against women in both physical and virtual spaces, while stressing the urgent need for stricter enforcement, awareness, and legal reforms to ensure women’s dignity, safety, and constitutional protection.